Salter Harris Fractures of the Distal Femur - Sean M. McKenna; Steven W. Hamilton; Simon L. Barker (SAGE Publishing, 2013)
Salter Harris-type injuries of the distal femur should be treated as a dislocation of the knee and therefore as a medical emergency. Senior medical staff should be involved early, ankle-brachial index ratio should be measured in all patients and the clinician should have a high index of suspicion for a vascular injury. Ideally reduction, stabilization, and vascular repair, if necessary, should be carried out within 6 hours of the initial event. There should be a low threshold for fasciotomies. These 2 cases demonstrate the importance of having a high index of suspicion for vascular injury and the need for continued reassessment.